The APA Publication Manual: Changes in the Seventh Edition. (April 2020) - Bradley, Loretta; Noble, Nicole; Hendricks, Bret
The Publication Manual of the American Psychological Association ( APA Publication Manual, Manual ) is a challenge for many counselors. The seventh edition (latest edition) of the Manual, published in October, 2019, has several changes. To demystify the changes, this article describes the major changes between the sixth and seventh editions of the Manual . The authors first describe the changes and then follow the changes with a table that highlights and contrasts the changes. The major premise of this article is that regardless of whether the counselor is a writer or reader of articles and books, the counselor should be familiar with the APA Publication Manual .